Public Trust in Health Care System in the Kurdistan Region - Sarena Braim Hussein; Akram Abduljabbar Abdullah (QALAAI ZANIST JOURNAL, 2024)
The study aims to understand and measure people's trust in health care system in the Kurdistan Region, and knowing which part or structure of the system has higher confidence than others. Furthermore, the research intends to discuss doctors' relationships with patients, pharmacies, laboratories and radiation. The author relies on online survey to collect data, and concluded that three-fourths of the sample, 75%, believes that the health condition in the Kurdistan Region has never been that much bad. Also, a very high proportion believes that the health system always supports doctors against patients. In one hand, about 90% of the example mentioned that the ministry of health does not do its job as necessary, and on the other hand, they believe that doctors are more likely to work as businessmen rather than human beings.